(untitled) (Sciences & Technology. A, exactes sciences, 1999)
A local isolate of Aspergillus fumigatus (Fresenius) albino mutant obtained from rotten wood shavings, grew at 45°C on a solid medium containing cellulose as carbon source. This fungus can utilize a variety of lignocellulosic substrates, such as Kraft paper pulp, straw, microcrystalline cellulose and filter paper. The highest endoglucanase (CMC-ase), b-xylanase and b-glucosidase activities were obtained in shaken flasks at 45°C, with mainly oat straw as sole carbon source. CMC-ase and b-xylanase activities showed the highest values (3.50 U/ml and 33 U/mI) at pH 4.0 and 5.0 respectively, and 70°C. b-glucosidase activity was maximal at 65°C (43 U/ml ), CMC-ase and b-xylanase enzymes were active in a large pH spectrum (3.0 to 8.0) and showed high thermostability at 60°C and above, especially for CMC-ase.